The Effect Of Using Learning Media On Learning Motivation About Creed and Morals At Mas Ushuluddin Singkawang - Husyin Saputra; Syahruddin Usman; Abdul Rahman Sakka; Aslan Aslan (IJGIE (International Journal of Graduate of Islamic Education), 2025)
This study aims to analyze the effect of the use of learning media on the motivation to learn the subject of Akidah Akhlak at the Private Islamic Senior High School (MAS) Ushuluddin Singkawang. The significance of using efficient learning resources to boost students' motivation and interest in comprehending Akidah Akhlak topics serves as the study's backdrop. A quantitative approach with an experimental design is the research methodology employed. Questionnaires, teacher and student interviews, and observation were used to gather data. The data analysis technique is carried out in two stages, namely the first stage with descriptive statistical analysis and the second stage is inferential statistical analysis. According to the study's findings, using interactive and diverse learning resources helps pupils become more motivated to learn. Compared to traditional techniques, students who use learning media are more engaged, passionate, and demonstrate greater comprehension. Based on the results of the questionnaire on the use of learning media, 68 respondents who were the subjects of the study, 26 respondents (38%) answered the use of learning media in the less category, 14 respondents (21%) answered the use of learning media in the moderate category, and 28 respondents (41%) answered the use of learning media in the high category. Then, based on the results of the questionnaire on learning motivation, it can be seen that 68 respondents who were the subjects of the study, 27 respondents (40%) had less motivation, 14 respondents (20%) had sufficient motivation, and 27 respondents (40%) had good motivation. Thus, this study recommends the use of learning media as a strategy to increase the effectiveness of learning Akidah Akhlak at MAS Ushuluddin Singkawang.